Frontispiece: Enantiodivergent Kinetic Resolution of 1, 1′‐Biaryl‐2, 2′‐Diols and Amino Alcohols by Dipeptide‐Phosphonium Salt Catalysis Inspired by the Atherton–Todd Reaction. Issue 27 (18th June 2021) - Fang, Siqiang; Tan, Jian‐Ping; Pan, Jianke; Zhang, Hongkui; Chen, Yuan; Ren, Xiaoyu; Wang, Tianli
Abstract : Asymmetric Catalysis The enantiodivergent kinetic resolution of 1, 1′‐biaryl‐2, 2′‐diols and amino alcohols by dipeptide‐phosphonium salt catalysis is reported by Tianli Wang et al. in their Research Article on page 14921